Bandgap engineering in two-dimensional halide perovskite Cs3Sb2I9 nanocrystals under pressure. Issue 3 (8th January 2020) - Geng, Ting; Ma, Zhiwei; Chen, Yaping; Cao, Ye; Lv, Pengfei; Li, Nan; Xiao, Guanjun
Abstract : The band gap narrowing of two-dimensional halide perovskite Cs3 Sb2 I9 nanocrystals was achieved under pressure. Abstract : Halide perovskites have attracted great attention owing to their outstanding performance in optoelectronic applications and solar cells. Recently, two-dimensional (2D) Cs3 Sb2 I9 nanocrystals (NCs) have attracted sustained interest due to their potentially useful photovoltaic behavior. However, their practical application is impeded by the large bandgap. In this study, the bandgap of 2D Cs3 Sb2 I9 NCs is successfully narrowed from 2.05 eV to 1.36 eV by means of a high pressure with a measurable rate of 33.7%. Optical changes of 2D Cs3 Sb2 I9 NCs originate from Sb–I bond contraction and I–Sb–I bond angle changes within the [SbI6] 3− octahedra, which determines the overlap of orbitals. Angle dispersive synchrotron X-ray diffraction spectra and Raman spectra of Cs3 Sb2 I9 NCs indicate that the structural amorphization gradually begins at about 14.0 GPa and the changes are reversible once pressure is completely released. The band gap is slightly smaller after decompression than that under the initial ambient conditions, resulting from the incomplete recrystallization process. First-principles calculations further elucidate that variations in band gaps are mainly governed by the orbital interactions associated with the distortion of the Sb–I octahedral network upon compression. The research enhances the fundamental understanding of 2D Cs3 Sb2 I9 NCs and is expected to greatly advance the research progress of perovskites in band gap interception at high pressures. Meanwhile, this study demonstrates that pressure processing can be used as a robust strategy to improve materials-by-design in applications.